On a class of non-ergodic Lotka–Volterra operator - Pah, Chin Hee; Rosli, Azizi (Pleiades Publishing, 2022)
In present paper, we study dynamical systems generated by a class of Lotka–Volterra operators. It is proved that such class of operator has non-ergodic property.